Gago Coutinho and the Scientific Navigation - Silva, André (2022)
Gago Coutinho, jointly with another Portuguese aerial navigator, managed to perform the First Flight from Europe to the South Atlantic in 1922, a Journey exclusively guided by internal means of navigation. Despite Coutinho being a person with multi-purpose activity on several areas of knowledge, he became known and glorified in the World in 1922, as an air navigator, a position that he achieved due to an aerial navigation device that he also had invented. Coutinho developed a new sextant model that could be used to measure the altitude of a star (when flying overseas) without the need of the sea horizon. This new device was called precision sextant and was provided with an artificial horizon line defined with the help of a water bubble. Due to his knowledge of Navigation, Astronomy, Geography and Mathematics, Coutinho received from the Portuguese King D. Carlos I, several assignments at Africa and Asia. Gago Coutinho received several important official medals and prizes, including the Ph.D. Honoris Causa from the Universities of Lisbon and Oporto and authored several scientific publications. Coutinho received the distinct position of Admiral of the Portuguese Navy in 1958 and died in the following year.